Ethnobotany of the Caucasus: A Book Review - Malik, Zubair A. (Ethnobotany Research and Applications, 2021)
Ethnobotany of the Caucasus. Bussmann, Rainer W., ed. 2017. Springer Nature, Cham, Switzerland. xxviii +746 pp. (hardcover). USD 299.00. ISBN 978-3-319-49411-1; DOI 10.1007/978-3-319-49412-8